PREGNANCY IN WOMEN WITH A HISTORY OF BREAST CANCER - A. A. Parokonnaya; M. I. Nechushkin; L. N. Lyubchenko; E. B. Kampova-Polevaya (ABV-press, 2014)
The study has demonstrated that medical abortion in women with a history of breast cancer is not justified as a medical intervention in further pregnancy. After 2 years of the termination of treatment, there may be procreation in a patient with early cancer, a good prognosis, and an active wish to have a baby. At the same time, the patient should undergo a complete examination, involving a geneticist's counseling.